A worldwide catalog of the Vermileonidae (Diptera: Brachycera) - Bueno, Gabriel M.; Kehlmaier, Christian; Santos, Charles Morphy D. (Zootaxa, 2021)
The genera and species of worldwide wormlions (Diptera: Rhagionidae) are listed, with annotated references to nomenclature, synonymies and generic combinations, type localities, primary type depositories, distribution, and citations for the most recent revisions. The most diverse genera of the family are Vermileo Macquart, Vermipardus Stuckenberg and Lampromyia Macquart, with 13 described species each. The bulk of Vermileonidae diversity, with nearly half of the valid species, remains in the Afrotropical region.